7-3(x-6)=5x-5

Simple and best practice solution for 7-3(x-6)=5x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-3(x-6)=5x-5 equation:


Simplifying
7 + -3(x + -6) = 5x + -5

Reorder the terms:
7 + -3(-6 + x) = 5x + -5
7 + (-6 * -3 + x * -3) = 5x + -5
7 + (18 + -3x) = 5x + -5

Combine like terms: 7 + 18 = 25
25 + -3x = 5x + -5

Reorder the terms:
25 + -3x = -5 + 5x

Solving
25 + -3x = -5 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
25 + -3x + -5x = -5 + 5x + -5x

Combine like terms: -3x + -5x = -8x
25 + -8x = -5 + 5x + -5x

Combine like terms: 5x + -5x = 0
25 + -8x = -5 + 0
25 + -8x = -5

Add '-25' to each side of the equation.
25 + -25 + -8x = -5 + -25

Combine like terms: 25 + -25 = 0
0 + -8x = -5 + -25
-8x = -5 + -25

Combine like terms: -5 + -25 = -30
-8x = -30

Divide each side by '-8'.
x = 3.75

Simplifying
x = 3.75

See similar equations:

| (1/4)y-(1/2)=(1/9) | | 4(6x+3)=300 | | 21-3x=4x | | 2x^6-10x^4+10=0 | | 4(6x+3)=3003 | | 4x=6.8 | | 4(x-1)-6=6x-2(4+x) | | 8(2x-6)=5(3x-7) | | f(x)=300x-5x^2+5 | | 3-4(x-3)=3x-12 | | 3(6+6x)=234 | | 8x+5y=1600 | | 30=x+.06x | | f(x)=300x-5x^2-5 | | F(0)=4x^2-9x+8 | | -40-(-53)= | | =300x-5x^2-5 | | 2a^4-5a^3-2a^2+10a-4=0 | | 2(x-7)+x=11 | | 5-x+2x-29=4x-34 | | (6*x)/2-6*5=(6*x)/3 | | 2(10+5x)=50 | | 29-3b+b^2=0 | | 7-6(x-5)=2x-9 | | M-[2-(2-m)]= | | 3x+7=3(x+8) | | a^4+2a^2-63=0 | | 7(1+2x)=161 | | 1-9B^2= | | -3s-10+s^2=0 | | 1000+5000x=12000 | | 5-5x=-4x+2 |

Equations solver categories